Analisis Analisis Pengaruh Pressure, Opportunity, Rationalization Dan Capability Terhadap Financial Statement Fraud Pada Perusahaan Manufaktur Di Bursa Efek Indonesia - Rivi Ferdila Trisna (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2022)
This study examines the level of influence of Pressure, Opportunity, Rationalization, and Capability on Financial Statement Fraud in Manufacturing Companies on the Indonesia Stock Exchange. This study uses a quantitative descriptive method. In obtaining research data, conduct a literature study. Related to this, the population of this study is all Manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the period 2016 to 2021. In determining the number of samples, this study uses the saturated sampling method. Where based on saturated sampling, researchers will use the entire population as the research sample. After that, the researcher will analyze the research data using the Logistics Regression method. The results showed that the variables of Financial Stability, External Pressure, Financial Target, Ineffective Monitoring, and Capability had an effect on Financial Statement Fraud. While the variables Nature of Industry, Change in Auditor, and Total Accrual Ratio have no effect on Financial Statement Fraud. This research proves that there is a need to increase company supervision, mitigate risks from pressures originating from Financial Stability, External Pressure, and Financial Targets of a company.